New American stories - Marcus, Ben, 1967- (Vintage contemporaries original., 2015)
"Ben Marcus, one of the most innovative and vital writers of this generation, delivers a stellar anthology of the best short fiction being written today in America In New American Stories, Ben Marcus has collected a diverse, exciting, and wholly unique book of contemporary American fiction writers. Herein are the luminaries of the form like Deborah Eisenberg, George Saunders, and Denis Johnson, as well as the best new voices of today, like Wells Tower, Claire Vaye Watkins and Rivka Galchen. Practitioners of deep realism like Anthony Doerr and Yilun Li brush shoulders with genre-bending wonders like Charles Yu and Kelly Link. Finally there are the true emerging stars, like Tao Lin and Rachel Glasser standing next to long established writer like Joy Williams. Nothing less than the American short story renaissance distilled down to its most relevant, daring, and interesting works, New American Stories puts on wide display the true art of the short story"--